Concepções e percepções de educação do campo na Escola Municipal Boa Esperança Sorriso – MT - Porto, Itamar (2016)
This study was carried out during the biennium 2014-2015, whose line of research was: Social movements , Political and Popular Education, through the intermediary of the Post Graduate Program in Education – PPGE, of the Federal University of Mato Grosso, having as theme: Conceptions and Perceptions of the Rural education in the Municipal School Boa Esperança , in Sorriso – MT. The aim of this study is to describe , understand and interpret the conceptions and perceptions of parents, teachers , administrators and students about the rural education, developed in the District of Boa Esperança, Sorriso – MT. To do so, we’ll discuss the concepts of Rural’s Education and school , curriculum , formation of rural’s teachers, from the struggles of social movements for a rural education and no education for the rural area , as well as the public policies that guarantee the rural education as a teaching mode. To do this research we used the qualitative approach of phenomenological nature, having as collection method observation, semi-structured interview, documentary analysis and bibliography. This study analyzes how rural education is being developed at the Municipal School Boa Esperança, especially the issues related to the institutional curriculum, the pedagogical projects and the formation of teachers to act in the rural education. Based on this research it was possible to describe the curriculum , the teacher’s formation and pedagogical projects developed in the aforesaid School, and demonstrate the formation programs that the County offers to the rural’s teachers.In synthesis , this study points to the need for readjustment of school curriculum, for the proposed existence of teacher’s rural formation and the pressing restructuring of the Political Pedagogical Project to the reality of the rural area, as well as highlight the school's own identity.